2014
DOI: 10.1261/rna.043653.113
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-omics of the human ribosome

Abstract: The torrent of RNA-seq data becoming available not only furnishes an overview of the entire transcriptome but also provides tools to focus on specific areas of interest. Our focus on the synthesis of ribosomes asked whether the abundance of mRNAs encoding ribosomal proteins (RPs) matched the equimolar need for the RPs in the assembly of ribosomes. We were at first surprised to find, in the mapping data of ENCODE and other sources, that there were nearly 100-fold differences in the level of the mRNAs encoding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 66 publications
5
81
0
Order By: Relevance
“…As hinted in previous reports [16, 50], we found that human tissues display a notable level of RP expression heterogeneity (Fig. 2), with around one quarter of all RP genes exhibiting tissue-specific expression.…”
Section: Discussionsupporting
confidence: 86%
“…As hinted in previous reports [16, 50], we found that human tissues display a notable level of RP expression heterogeneity (Fig. 2), with around one quarter of all RP genes exhibiting tissue-specific expression.…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown that several ribosomal proteins are expressed in a tissue-specific manner [107]. Moreover, loss of certain ribosomal protein(s) only impairs specific tissue(s) [50]. These observations lead to the speculation that the structure/composition of ribosome varies from one tissue to another [50].…”
Section: Motivation Behind This Thesismentioning
confidence: 99%
“…Moreover, loss of certain ribosomal protein(s) only impairs specific tissue(s) [50]. These observations lead to the speculation that the structure/composition of ribosome varies from one tissue to another [50]. Therefore the interaction networks of ribosomal proteins should also vary in a cell/tissue-specific manner.…”
Section: Motivation Behind This Thesismentioning
confidence: 99%
See 2 more Smart Citations